2011
DOI: 10.1111/j.1365-246x.2011.05041.x
|View full text |Cite
|
Sign up to set email alerts
|

Mantle wedge hydration in Nicaragua from local earthquake tomography

Abstract: S U M M A R YThe continental margin of Nicaragua and Costa Rica is characterized by significant lateral changes from north to south such as a decreasing dip of the slab, a decreasing magma production and a shift in the volcanic front. To investigate this transition, a joint on-and offshore local earthquake tomography was performed. Low P-wave velocities and high V p /V s ratios, indicative for hydration, were found in the upper-mantle and lowermost crust beneath the Sandino Basin. The mantle wedge hydration ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 75 publications
(204 reference statements)
1
22
0
Order By: Relevance
“…As such it can be expected that it differs from its surrounding rock units rheologically as well as in terms of seismic velocity. Early as well as recent seismic investigations have shown that ≥15% seismic velocity reduction, corresponding to ≥20% serpentinization, can easily be expected in fractured oceanic lithosphere [e.g., White et al , 1984; Calvert and Potts , 1985; Ivandic et al , 2010; Dinc et al 2011]. …”
Section: Discussionmentioning
confidence: 99%
“…As such it can be expected that it differs from its surrounding rock units rheologically as well as in terms of seismic velocity. Early as well as recent seismic investigations have shown that ≥15% seismic velocity reduction, corresponding to ≥20% serpentinization, can easily be expected in fractured oceanic lithosphere [e.g., White et al , 1984; Calvert and Potts , 1985; Ivandic et al , 2010; Dinc et al 2011]. …”
Section: Discussionmentioning
confidence: 99%
“…Unusually deep earthquakes have been identified both in subduction zones (e.g., DINC et al, 2011) and in rift zones (e.g., LINDENFELD AND RÜ MP-KER, 2011). The generation of such earthquakes was related to the presence of water in these geodynamical systems (dehydration reactions in the subducting plates) or to deep magmatic processes in the rift structures.…”
Section: Discussionmentioning
confidence: 99%
“…Seismic structure beneath Costa Rica and Nicaragua has been investigated in a number of tomographic studies based on data acquired by several temporary networks [e.g., Colombo et al , 1997; Protti et al , 1999; Yao et al , 1999; Sallarès et al , 2000; Quintero and Kissling , 2001; Husen et al , 2003; Arroyo et al , 2009; Dinc et al , 2010, 2011]. Most of the different authors applied independent approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The crust and lithospheric mantle of the overriding plate shows regionally variable velocities which could be associated with major tectonic units and local structure such as subducting seamounts. A pronounced minimum of velocity and increased Vp/Vs ratios are found in southern Nicaragua suggesting a significant hydration of the mantle wedge [ Dinc et al , 2010, 2011].…”
Section: Introductionmentioning
confidence: 99%